The Role of Social Media Influencer Communication in Influencing the Attitudes and Consumer Behavior of Generation Z in Urban Areas - Nur Alam; Ayat Taufik Arevin; Murdiansyah Herman (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study examines the role of social media influencer communication in shaping the attitudes and consumer behavior of Generation Z in urban areas. As digital natives, Generation Z is highly influenced by social media content, particularly that which is delivered by influencers across platforms such as Instagram, YouTube, and TikTok. This generation values authenticity and relatability, and influencers who exhibit these qualities significantly impact their purchasing decisions and brand perceptions. Using a qualitative approach, this research synthesizes existing literature on influencer marketing, consumer behavior, and Generation Z, identifying key trends such as the importance of trust and credibility in influencer communication. The study finds that social media influencers, through their perceived authenticity, have a profound effect on Generation Z's consumer attitudes, leading to changes in brand loyalty and purchase intentions. Additionally, the research highlights that influencers’ ability to foster a sense of community and connection further amplifies their influence. The findings underscore the growing significance of influencers in the marketing strategies targeting Generation Z, especially in urban areas where digital content consumption is prevalent.